Formulation of Arrangements for Not Achieving Work Targets of Workers/Laborers as a Reason for Termination of Work Relationships - Winarsi, Sri; Nugraha, Xavier; Arjuna, Gio; Putri, Dita Elvia Kusuma (Jurnal Ketenagakerjaan, 2024)
Article 154A of Law of the Republic of Indonesia No. 13 of 2003 on Manpower and Article 36 of Government Regulation No. 35 of 2021 on Fixed-term Employment Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment have regulated the reasons for termination of employment in a limitation and enumerative. However, there is a legal vacuum regarding the non-fulfillment of targets by workers or laborers as a reason for termination of employment, even though employers often use this reason. Based on these legal issues, the problem formulation in this article is first, how is the validity of not achieving sales targets as a reason for termination of employment? Second, what are the legal considerations of the Panel of Judges regarding the non-achievement of sales targets as a reason for termination of employment? This research is a normative legal research with statutory, conceptual, and case approaches. The results of this research are first, the reason for termination of employment related to the non-fulfillment of targets by workers or laborers can be used as a reason for termination of employment if the reason is regulated in the Work Agreement, Company Regulation, or Collective Labor Agreement and has previously been given the first, second, and third warning letters consecutively each valid for a maximum of 6 (six) months unless otherwise stipulated in the Work Agreement, Company Regulation, or Collective Labor Agreement. Secondly, based on existing court decisions, the reasons for termination of employment related to non-fulfillment of targets by workers or laborers are valid.